2020
DOI: 10.1242/dmm.042549
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish models of skeletal dysplasia induced by cholesterol biosynthesis deficiency

Abstract: Human disorders of the post-squalene cholesterol biosynthesis pathway frequently result in skeletal abnormalities, yet our understanding of the mechanisms involved is limited. In a forwardgenetic approach, we have found that a late-onset skeletal mutant, named koliber nu7 , is the result of a cis-acting regulatory mutation leading to loss of methylsterol monooxygenase 1 (msmo1) expression within pre-hypertrophic chondrocytes. Generated msmo1 nu81 knockdown mutation resulted in lethality at larval stage. We dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 100 publications
(139 reference statements)
0
6
0
Order By: Relevance
“…Although studies have reported increased expression of TXNRD1 and SRXN1 in protective iron overload heart and kidney tissues due to activation of the NRF2 signaling pathway, their expression was decreased in IPAH lung samples we analyzed, which may be due to much higher levels of iron overload and the presence of oxidative stress activated by other factors [51][52][53][54][55]. The increased expression of TSPAN5 may be related to the activation of the NOTCH signaling pathway by increased cellular uptake of iron, while the downregulation of MSMO1 expression may be mechanistically related to heme metabolism, but relevant studies are lacking [56][57][58][59]. In addition, intracellular iron overload usually leads to downregulation of BCL2 and induces apoptosis; interestingly, the expression of BCL2 was upregulated in the IPAH lung samples we analyzed, which may result in abnormal antiapoptotic phenotypic changes in pulmonary vascular endothelial cells and pulmonary vascular smooth muscle cells due to factors other than iron metabolism [60][61][62].…”
Section: Discussionmentioning
confidence: 94%
“…Although studies have reported increased expression of TXNRD1 and SRXN1 in protective iron overload heart and kidney tissues due to activation of the NRF2 signaling pathway, their expression was decreased in IPAH lung samples we analyzed, which may be due to much higher levels of iron overload and the presence of oxidative stress activated by other factors [51][52][53][54][55]. The increased expression of TSPAN5 may be related to the activation of the NOTCH signaling pathway by increased cellular uptake of iron, while the downregulation of MSMO1 expression may be mechanistically related to heme metabolism, but relevant studies are lacking [56][57][58][59]. In addition, intracellular iron overload usually leads to downregulation of BCL2 and induces apoptosis; interestingly, the expression of BCL2 was upregulated in the IPAH lung samples we analyzed, which may result in abnormal antiapoptotic phenotypic changes in pulmonary vascular endothelial cells and pulmonary vascular smooth muscle cells due to factors other than iron metabolism [60][61][62].…”
Section: Discussionmentioning
confidence: 94%
“…We also observed coordinated expression of cholesterol biosynthesis, with maximal expression of 17 metabolically central genes at stage 25 before being downregulated at later stages (Figure 3F). Cholesterol plays important roles in the transduction of hedgehog signalling (S. Xu and Tang 2022; Stottmann et al 2011) and is required for the correct development of muscle and bone (Campos et al 2015; Anderson et al 2020). Sonic hedgehog (SHH) is secreted by the notochord and controls the specification of the sclerotome during patterning of epithelial somites (Murtaugh, Chyung, and Lassar 1999).…”
Section: Resultsmentioning
confidence: 99%
“…Squalene epoxidase a ( sqlea ) catalyzes the first oxygenation step in cholesterol biosynthesis and is thought to be one of the rate-limiting enzymes in this pathway ( 51 ). Methylsterol monooxygenase 1 ( msmo1 ) plays a role in cholesterol biosynthesis in the liver ( 52 ). cyp51 (sterol 14α-demethylase), as a cytochrome P450, is crucial for biosynthesis reaction of sterols and serves as a drug target in the clinic ( 53 ).…”
Section: Resultsmentioning
confidence: 99%